Deciphering Financial Health and Risk: Hierarchical Relationships and Interdependencies among Key Factors - Jain, Mayank; Malik, Taniya (Asosiasi Fakultas Ekonomi dan Bisnis Indonesia, 2023)
This study investigates the hierarchical relationships and interdependencies among various financial factors influencing companies' health. By employing Total Interpretive Structural Modeling (TISM) and Matrice d'Impacts Croisés Multiplication Appliquée à un Classement (MICMAC) analyses, the research identifies vital financial factors and their mutual influences. The study's primary findings reveal credit risk as a pivotal, independent factor with a substantial impact on other financial parameters. Furthermore, solvency, capital adequacy, and Tier 1 capital ratios emerge as fundamental determinants of a company's financial health. The MICMAC analysis classifies financial factors into four categories: independent, linkage, autonomous, and dependent. This research offers valuable insights for managers, policymakers, and investors in understanding the financial health of companies, enabling them to make well-informed decisions focusing on critical factors such as credit risk, solvency, and liquidity.